Declining child mortality in northern Malawi despite high rates of infection with HIV - A Jahn; S Floyd; AC Crampin; H Mvula; V Mwinuka; E Mwaiyeghele; N McGrath; B Zaba; PEM Fine; JR Glynn (The World Health Organization, 2010)
OBJECTIVE: To determine whether routine surveys, such as the Demographic and Health Surveys (DHS), have underestimated child mortality in Malawi. METHODS: Rates and causes of child mortality were obtained from a continuous-registration demographic surveillance system (DSS) in Malawi for a population of 32 000. After initial census, births and deaths were reported by village informants and updated monthly by project enumerators. Cause of death was established by verbal autopsy whenever possible. The likely impact of human immunodeficiency virus (HIV) infection on child mortality was also estimated from antenatal clinic surveillance data. Overall and age-specific mortality rates were compared with those from the 2004 Malawi DHS. FINDINGS: Between August 2002 and February 2006, 38 617 person-years of observation were recorded for 20 388 children aged < 15 years. There were 342 deaths. Re-census data, follow-up visits at 12 months of age and the ratio of stillbirths to neonatal deaths suggested that death registration by the DSS was nearly complete. Infant mortality was 52.7 per 1000 live births, under-5 mortality was 84.8 per 1000 and under-15 mortality was 99.1 per 1000. One-fifth of deaths by age 15 were attributable to HIV infection. Child mortality rates estimated with the DSS were approximately 30% lower than those from national estimates as determined by routine surveys. CONCLUSION: The fact that child mortality rates based on the DSS were relatively low in the study population is encouraging and suggests that the low mortality rates estimated nationally are an accurate reflection of decreasing rates.